A Contextual Application of Matthew 25:14-30 as a Framework for Business Ethics in the Nigerian Society - Okoh, Blessing Uenosen; Osajie, Justina Nwazuni (NIU Journal of Management Sciences, 2026)
The paper considers the Parable of the Talents, Matthew 25:14-30, as a source of business ethics, its applicability in the modern business world. The core themes of the parable, stewardship, accountability and risk-taking are examined exegetically, theologically and sociologically, considering the original 1st-century Palestinian setting. The study uses textual, historical, theological (themes of grace and judgment) and comparative (with contemporary ethical perspectives including utilitarianism and stewardship ethics) analyses in its methodology. The research explores the lessons of the parable for business and explores the compatibility of profit motives and ethical stewardship, the spirit of responsible investment vs complacency and the need for corporate responsibility. Examples from the firms Enron, Volkswagen, Patagonia and TOMS Shoes are discussed. The article also explores Kantian duty, its relation to Islamic and Jewish ethics on financial matters.  It also explores criticisms and difficulties of the parable's application to business, and potential cultural biases. The analysis shows the parable's ability to provide tremendous ethical lessons for today's business challenges. Finally, this paper emphasises the eternal virtues of stewardship, accountability and risk-taking that help to guide business practices. The research, therefore, suggests policymakers and business leaders can work together to develop rules and guidelines that promote ethical stewardship and accountability and a business climate that emphasises sustainability and social responsibility. Keywords: Contextual, Application, Matthew 25:14-30, Framework, Business and Ethics